2021
DOI: 10.3389/fbioe.2021.782355
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Signaling in Osteoblasts is Required for Mechanotransduction in Bone Fracture Healing

Abstract: Biomechanical stimulation by whole-body low-magnitude high-frequency vibration (LMHFV) has demonstrated to provoke anabolic effects on bone metabolism in both non-osteoporotic and osteoporotic animals and humans. However, preclinical studies reported that vibration improved fracture healing and bone formation in osteoporotic, ovariectomized (OVX) mice representing an estrogen-deficient hormonal status, but impaired bone regeneration in skeletally healthy non-OVX mice. These effects were abolished in general es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
(101 reference statements)
1
3
0
Order By: Relevance
“…Whole-body low-magnitude high-frequency vibration (LMHFV) promoted fracture healing in OVX mice, but it had no or opposite effects in healthy mice. This observation suggests that the response of the bony callus to stress stimulation is more sensitive in estrogen-depleted mice than in normal mice [ 10 ] and supports our findings that there were no significant differences in the phenotypes of the anterior and posterior calluses in the OVX group. This indicates that, even though the fixed pin may cause abnormally reduced stress, it can still stimulate bone repair without a site-specific inconsistent manner in estrogen deficiency mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Whole-body low-magnitude high-frequency vibration (LMHFV) promoted fracture healing in OVX mice, but it had no or opposite effects in healthy mice. This observation suggests that the response of the bony callus to stress stimulation is more sensitive in estrogen-depleted mice than in normal mice [ 10 ] and supports our findings that there were no significant differences in the phenotypes of the anterior and posterior calluses in the OVX group. This indicates that, even though the fixed pin may cause abnormally reduced stress, it can still stimulate bone repair without a site-specific inconsistent manner in estrogen deficiency mice.…”
Section: Discussionsupporting
confidence: 90%
“…The peak expression of estrogen receptors in the bony callus of OVX-induced osteoporotic fractures was delayed compared to normal fractures. However, stress stimulation in the absence of estrogen promoted the expression of estrogen receptor α and thus increased bone formation [ 9 , 10 ]. These may explain the higher bone volume of the posterior scab in the OVX group compared to the anterior side 28 d post fracture (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that inhibition of estrogen receptor-α (ER-α) expression suppresses osteoblast differentiation. Several studies in cell culture and animal models of ER-α-knockout mice demonstrate a critical role of the osteoblast ER-α in bone regeneration and fracture healing [6][7][8].…”
Section: The Main Pathogenetic Factors Of Osteoporosis 21 Estrogen De...mentioning
confidence: 99%